Performance appraisal of a small wind turbine under the use of three rotor hub configurations - Jouchi, Abbas Akbari; Pourrajabian, Abolfazl; Rahgozar, Saeed; Dehghan, Maziar (Clean technologies and environmental policy, 2023)
Small wind turbine blades are generally designed without accounting for geometric attributes of the rotor hub configuration. The present study quantitatively investigates how the inappropriate hub configuration could worsen the performance of blades whose geometry is separately designed in the optimization procedure. For that purpose, three hub configurations were proposed for the first time and the performance of a 1 kW three-bladed turbine was investigated in terms of the power coefficient and the starting time. While the former is the main and the most important parameter for small turbines, the latter is also of utmost importance as these turbines are not generally fitted with the pitch control mechanism, giving rise to the starting delay. Of the considered configurations, results show a delay of 8% in starting for the worst case with respect to the best one which is mainly due to the increase in the rotor inertia. More importantly, the corresponding value for the power coefficient loss could be as high as 21%, mainly due to the change in the aerodynamic properties of the blades sections (airfoils). Therefore, the results present a strong case for the necessity of coupling the hub configuration with the blades through the design of small rotors. Also carried out in the study was the structural analysis of the proposed hubs under the involved loadings. The analysis performed by the finite element method approved the applicability of the proposed configurations from the structural aspect. Graphical abstract